KESAKSIAN PEREMPUAN DALAM AL-QUR’AN PERSPEKTIF ASGHAR ALI ENGINEER: PEMBACAAN FENOMENOLOGI HERMENEUTIK PAUL RICOEUR: PAUL RICOEUR'S HERMENEUTIC PHENOMENOLOGICAL READING - Nada Rahmatina (Department Islamic Education, Faculty of Education and Teacher Traning, Universitas Islam Bandung, 2024)
Discussions about gender issues in contemporary times are never-ending topics, including in the realm of Islamic studies. This study examines women's testimonies in Asghar Ali Engineer's thoughts, which are analyzed using Paul Ricoeur's hermeneutical phenomenological framework. Engineer's thoughts regarding women's testimony are important to discuss because of the dismantling of the discourse he carried out regarding verses with gender connotations in the Al-Qur'an, which often do not follow the mainstream interpretation. This research is library research with qualitative research methods. The primary source for this research is Asghar Ali Engineer's interpretation of verses from women's testimonies, while the secondary sources used are other literature sources that are relevant to the research, both in the form of books and journal articles. This research aims to track and explore Asghar Ali Engineer's thoughts regarding the verses in women's testimonies. The author uses Paul Ricoeur's hermeneutic phenomenology theory in analyzing Asghar Ali's thoughts. The results of this research were the engineer's re-reading of the verse about women's testimony, namely QS. Al-Baqarah/2: 282. In Paul Ricoer's concept of hermeneutical phenomenology, engineers go through a process of decontextualization-recontextualization in order to obtain new meanings that are relevant to the current context. In the decontextualization process, Engineer explained the socio-cultural conditions at the time the verse was revealed, which implied that women lacked knowledge and experience regarding business, so that one additional female witness was needed as a reminder, and it did not fully mean that women's status was half that of men. The recontextualization process includes three stages, namely semantic, reflexive, and existential. In the modern context where women are more educated about financial matters, even more so than men, there is nothing to prevent a woman's position as a witness from being equal to that of a man.